A new species of the eelpout genus Ophthalmolycus (Teleostei, Zoarcidae) from off South Orkney Islands, Weddell Sea - Prokofiev, Artem M.; Kobyliansky, Stanislav G.; Orlov, Alexei M. (Zootaxa, 2025)
Ophthalmolycus lacrimegalos sp. nov. is described from a single specimen collected off the South Orkney Islands, Weddell Sea, Southern Ocean at a depth of 1,495 m. The new species differs from its congeners by the combination of extensive squamation covering the abdomen, predorsal area, and pectoral axil; an enlarged lachrymal bone, a wide bony interorbital space, and other characters (cephalic pore configuration, meristics, body proportions, coloration, etc.) in combination. This is the sixth species of the genus in the Antarctic waters, bringing the total number of known species in the genus to ten. However, the distinction of Ophthalmolycus in its current composition from the species-rich genus Lycenchelys requires elucidation. A revised key to the species of Ophthalmolycus is provided.